The Influence of Indoor Environments in Respiratory Health and Quality of Life of Susceptible Populations - The GERIA Project - Mendes, A. (2017)
Presentation about GERIA Project “Geriatric Study in Portugal on Health Effects of Air Quality in Elderly Care Centers. The aim of GERIA project is to carry out a risk assessment involving: identification of multiple factors potentially affecting health and quality of life; quantification of human exposure to pollutants, and evaluation of the individual’s response to these stimuli.